THE APPLICATION OF MURDER TECHNIQUE TO IMPROVE READING COMPREHENSION - Ni Wayan Krismayani, (SPHOTA: Jurnal Linguistik dan Sastra, 2015)
ABSTRACT Reading is a complex process involving skill and intelligence in which readers make sense of the text by combining their prior knowledge, purpose of reading and the information given in the text. This study addresses some important point regarding MURDER technique in fulfilling the need of University student in reading comprehensively. The researcher then implemented MURDER (Mood, Understand, Recall, Detect, Elaborate, and Review) technique on his attempt to solve the problem face by the fourth semester students of English Education Study program FKIP Unmas denpasar in academic year 2014/2015. The classroom action research was carried out in two-planned cycles that were proceeded by administration of pre-test. The result of the tests, pre-test and post-tests, showed that the students’ reading comprehension improved significantly. To get the supporting data, structured questionnaire, showed positive responses concerning the students’ responses toward the implementation of MURDER technique. These results were considered as the findings of this study. In conclusion, the findings of the present classroom action research have achieved the expected result, that was, improving the low level mastery of reading comprehension; furthermore, it can be, of course, accomplished because of the implementation of MURDER technique. Keyword: MURDER, reading comprehension.